Analisis masalah belajar siswa jurusan IPS di SMA Negeri Banda Aceh - Reka Mulya Castury; Nurhasanah Nurhasanah; Martunis Yahya (Program Studi Bimbingan dan Konseling, FKIP Universitas Syiah Kuala, 2019)
Abstract: Basically the selection of majors held in high school is an effort to develop students' abilities. However, in its implementation it actually caused discriminatory actions against the Social Sciences department so that a negative view appeared on them. This study was conducted to find out: (1) Learning problems faced by Social Sciences students, and (2) factors that influence students' learning problems. This study uses descriptive methods and quantitative approaches. The population is all students of Social Sciences majoring in class XI of Banda Aceh 3, 4 and 12 High Schools with 231 students. The sample of this study was 49 students. The data collection technique used the AUM-PTSDL questionnaire and the influencing factor questionnaire instrument. Analysis of AUM - PTSDL questionnaire data using the BK software program and questionnaire instruments using descriptive percentages. The results of the research in the three schools show that the most dominant learning problem is in the field of learning skills. Also found factors that influence learning problems are physical / child health factors, parenting / ways parents educate children and inadequate school facilities.Keywords: Learning problems, students of Social Science Department Abstrak: Pada dasarnya penjurusan yang dilaksanakan di SMA ialah sebagai upaya untuk mengembangkan kemampuan siswa. Namun, dalam pelaksanaannya justru menimbulkan tindakan diskriminatif terhadap jurusan IPS sehingga muncul pandangan negatif pada mereka. Studi ini dilakukan untuk mengetahui: (1) Masalah-masalah belajar yang dihadapi siswa jurusan IPS, dan (2) faktor yang mempengaruhi masalah belajar siswa. Penelitian ini menggunakan metode deskriptif dan pendekatan kuantitatif. Populasinya adalah semua siswa jurusan IPS kelas XI SMA 3, 4 dan 12 Banda Aceh sebanyak 231 siswa. Sampel penelitian ini sebanyak 49 siswa. Teknik pengumpulan data menggunakan angket AUM – PTSDL dan instrumen angket faktor yang mempengaruhi. Analisis data angket AUM – PTSDL mengggunakan program software BK dan instrumen angket menggunakan deskriptif presentase P+f:Nx100%. Hasil penelitian di ketiga sekolah tersebut memiliki masalah belajar paling dominan ialah di bidang keterampilan belajar dan faktor-faktor yang mempengaruhi masalah belajarnya ialah faktor jasmaniah/kesehatan anak, pola asuh/cara mendidik orangtua dan fasilitas sekolah yang kurang memadai.Kata kunci: Masalah Belajar, Siswa Jurusan IPS